IoT Solar Panel Tracking For I-V And P-V Characteristic - Gimin, Nor Arina; Nor Aira Zambri; Sim Sy Yi; Farahiyah Mustafa (Progress in Engineering Application and Technology, 2022)
This project presents and discusses techniques in monitoring and processing of I-V and P-V curves of photovoltaic modules. Usually, this problem occurs at all solar sites where collecting information or data on each solar panel become difficult due to its. The huge region and acreage of solar sites. Furthermore, some equipment has restricted or incorrect specifications, which might be compromised during data collecting. It is conceivable that the data collected is inaccurate. Therefore, this project aims to analyze, collect, and store I-V and P-V data on the solar panels at solar sites. This project combines an IoT system that consists of an Arduino systems and Wi- Fi module that allows, to analyze, collect and also store the voltage, current and power data from each solar panel. The Blynk system will serve as a medium for IoT systems to connect information to the users. Then, all the data from each solar panel can be displayed via phone and the data can be transferred through email. With this feature, all the data from the solar panel’s voltage, current and power can be displayed quickly and easily. Using this system, a lot of time can be saved compared to the one using data logger. In conclusion, this project can provide improvements to existing systems by notifying to the users about the required voltage, current and power data.